Research in the School: Theoretical and Methodological Reflections - Chaluh, Laura Noemi [UNESP] (My University, 2012)
In this work I socialize my experience as researcher in an elementary school in a city in the state of Sã o Paulo during two years. The presence in the school aimed to understand how teachers would re-create the public policy offormation that is established by the Secretary of Education of this City Hall. I participated in two formation groups composed by school teachers from the initial education levels and the management team. I collaborated with the educational work of two teachers in the classroom. The encounter with the school subjects led me to reflect on the meanings of my presence in the school, in particular, from the teachers considerations indicating the importance of dialogue, collaboration and help from the researcher in the school. This work presents theoretical and methodological contributions to understand to what end and why research in and with the school and highlights the need for researchers to assume a commitment to teachers, students and school. The work was developed from a qualitative study of socio-historical orientation that, from a dialogical perspective, considers the research as a relationship between subjects and the interaction plays a key role in the formation of subjectivities, allowing teachers and the researcher to create new meaning in the research process.
Keywords: research; research formation; teacher formation